Analisis Kemampuan Problem Solving Siswa pada Materi Eksponen Melalui PBL Berbasis Polya - Rusyda Auliya; Tahir Tahir; Chairuddin Chairuddin; Erfina Erfina (UIN Walisongo Semarang, 2025)
This study aims to analyze the problem-solving abilities of tenth-grade students at SMAN 1 Lalolae on the topic of exponents after the implementation of problem-based learning (PBL) with reference to Polya’s problem-solving stages. The background of this research is based on the limited number of studies that specifically examine students’ problem-solving skills in exponents through the application of PBL with a Polya-based approach. The research employed a descriptive qualitative method with ten students from SMAN 1 Lalolae selected using purposive sampling, representing high, medium, and low ability categories. Data were collected through problem-solving tasks on exponents and semi-structured interviews, then analyzed using Polya’s indicators, which include understanding the problem, devising a plan, carrying out the plan, and reviewing the solution. The findings indicate that high-ability students were able to solve problems systematically from understanding the problem to obtaining the correct solution, although the evaluation stage was not yet optimal. Medium-ability students were able to write down information and formulas but often struggled in selecting appropriate strategies, resulting in partially incorrect answers. Meanwhile, low-ability students encountered difficulties from the initial stage, demonstrated unclear strategies, and produced incorrect solutions. The findings suggest the need to develop scaffolding strategies to support students with moderate and low levels of ability. The application of PBL was proven to enhance students’ engagement and problem-solving abilities, although evaluation and reflection aspects still need improvement.